Beberapa Parameter Biokimia Darah Ayam Ras Petelur Fase Grower dan Layer dalam Lingkungan “Upper Zonathermoneutral” - A. Mushawwir; D. Latipudin (Universitas Andalas, 2011)
Twenty grower and laying hens housed indoors in individual cages were used to explore the profile to some biochemistry parameters on grower and laying hens in upper zonathermoneutral (average: 31.5oC). This study was conducted in poultry housing at CV. Pamulihan Farm Kuningan, Jawa Barat, for two months. Blood samples free protein were used to determined glucose, blood plasma for cholesterol, and blood serum were used to determined albumin, globulin and protein total. Biochemistry Parameters in this study were analyzed by spectrophotometer technique. Results of this study indicated that there were significantly effect of temperature on the albumin, globulin, total protein, and glucose. This results has been proved to be a good indicator for predicting heat stressed in laying hens. Based on this results of study, it may be a consideration for a good feed strategy to laying hens in upper zonathermoneutral.